2018
DOI: 10.1007/s10068-018-0406-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory functionality of ten Sri Lankan seaweed extracts obtained by carbohydrase assisted extraction

Abstract: Enzyme-assisted extraction is a cost-effective, safe, and efficient method to obtain bioactives from plant materials. During this study, 10 different marine algae from Sri Lanka were individually extracted by using five commercial food-grade carbohydrases. The enzymatic and water extracts of the seaweeds were analyzed for their antioxidant and anti-inflammatory activities. The highest DPPH, hydrogen peroxide (H 2 O 2 ) and intracellular H 2 O 2 scavenging abilities were observed from the Celluclast extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Our results also indicated a strong correlation (at P ≤ 0.05) between the antioxidant activity using DPPH, reducing power and TAC with the estimated total phenolic content of seaweeds which were in adherence to studies by Ismail et al (2016) and Ismail (2017). In addition, some studies reported the antioxidant activities of the seaweeds are associated with the phenolic algal content (Shanura Fernando et al, 2018). Nowadays, there is a growing concern on the discovery of natural antioxidants mainly because biologically active phytochemicals are largely more secure than manufactured synthetic analogies and for their conservative role in the improvement of disease like cancer, atherosclerosis, arthritis, diabetes, alzheimer's and aging (Santos-Sánchez et al, 2019).…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 89%
See 1 more Smart Citation
“…Our results also indicated a strong correlation (at P ≤ 0.05) between the antioxidant activity using DPPH, reducing power and TAC with the estimated total phenolic content of seaweeds which were in adherence to studies by Ismail et al (2016) and Ismail (2017). In addition, some studies reported the antioxidant activities of the seaweeds are associated with the phenolic algal content (Shanura Fernando et al, 2018). Nowadays, there is a growing concern on the discovery of natural antioxidants mainly because biologically active phytochemicals are largely more secure than manufactured synthetic analogies and for their conservative role in the improvement of disease like cancer, atherosclerosis, arthritis, diabetes, alzheimer's and aging (Santos-Sánchez et al, 2019).…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 89%
“…Also, the acetone extract of Sargassum wightii and the benzene extract of Sargassum polycystum exhibited DPPH antioxidant activity with 43% and 22%, respectively (Unnikrishnan et al, 2015). In a recent study, the Celluclast (a preparation used to degrade cellulose into glucose) enzymatic extract of Sargassum polycystum revealed a strong DPPH scavenging activity estimated to be 57.23% (Shanura Fernando et al, 2018).…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…With respect to the prevention and/or treatment of chronic inflammation, dietary compounds are receiving attention due to their safety and lack of adverse effects [26]. Among various dietary approaches, treatment with the edible oil RBO was investigated for its anti-inflammatory effects in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Following up on the preliminary screening [25], Sargassum polycystum samples for the mass extraction were collected from the south-west coast of Sri Lanka. After washing with tap water, the samples were lyophilized and ground into a powder.…”
Section: Collection and Extraction Of Fucoidan Rich Fractionmentioning
confidence: 99%